THE EFFECT OF INVESTMENT OPPORTUNITY SET, COMPANY AGE, LIQUIDITY, AND FINANCIAL LEVERAGE ON EARNINGS QUALITY - Widiyanti, Ade; Yunani, Selvi; Septiyanti, Ratna (Faculty of Economics and Business, 2025)
This study examines the effect of the Investment Opportunity Set (IOS), company age (Firm Age), liquidity, and financial leverage (Financial Leverage) on earnings quality in LQ45 Index companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. A quantitative approach is employed using multiple linear regression on secondary data from the annual financial statements of LQ45-listed companies. The results indicate that Investment Opportunity Set (IOS) has a significantly positive effect on earnings quality, implying that the greater a company's investment opportunities, the better its earnings quality. Firm Age has a positive but not significant effect, suggesting that older firms tend to have better earnings quality, although the effect is not statistically significant. Liquidity has a significantly negative effect, indicating that highly liquid firms tend to hold excessive cash, hindering profitability optimization and reducing earnings quality. Financial Leverage has a significantly positive effect, demonstrating that well-managed debt utilization enhances earnings quality. Simultaneously, Investment Opportunity Set, Firm Age, Liquidity, and Financial Leverage significantly influence earnings quality. These findings provide valuable insights for investors, financial analysts, and regulators in assessing factors affecting earnings quality and formulating more effective investment policies and financial strategies to enhance transparency and accuracy in financial reporting within capital markets.